Application of Villamil-Molina in Virtual Reality Environmental Information on The ITPLN Campus - Herman Bedi; Abdurrasyid; Meilia Nur Indah Susanti; Indrianto; M Yoga Distra Sudirman; Rahma Farah Ningrum; Yessy Asri; Joey Andrew Fransisco Sihombing; Azizah Arip Rambe (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
This study aims to apply Virtual Reality (VR) as an information medium in the ITPLN campus environment, focusing on the Villamil-Molina analysis method. The 3DVista app will be used as a VR content development platform. The research will evaluate accessibility, educational effectiveness, user acceptance, content availability, financial aspects, security, privacy, and environmental impact. The study results are expected to provide an in-depth understanding of the potential of VR, identify obstacles, and present recommendations to improve its implementation in the ITPLN campus environment by utilizing 3DVista applications. Villamil-Molina follows structured steps, uses the right creativity, and provides a satisfying experience for users.